The language of Menander Comicus and its relation to the Koiné - Cartlidge, B (2014)
The thesis is a study of the language of Menander Comicus (c.341-292/1 B.C.). The core of the thesis is a partial description of his language. Using a sociolinguistically informed model of koineisation, Menander's language is related to developments in the linguistic history of Greek. The first chapter therefore reviews the literature on Menander's language and details the theory of koineisation that will inform the subsequent chapters; accommodation theory is here of particular importance. The second chapter reviews nominal word-formation, used elsewhere in the literature as a criterion of the Koiné. It is pointed out that word-formation is not a good criterion, as the assessment of productivity patterns in a dead variety is difficult. However, by a detailed philological study of the data in Menander, some conclusions are reached about the productive and non-productive suffixes in Menander. The derivational patterns he attests for the most part look classical, but some changes are detected. The third chapter looks at the phonology and morphology of Menander. It is suggested that the vocalism of Menander betrays some characteristic Koiné developments, while the consonantism is mostly conservative. Noun and pronoun morphology are mostly conservative, while verbal morphology shows some signs of paradigm levelling. This is in line with the developments expected of a koineising variety, which are characterised by levelling. The final chapter is much more descriptive and focuses on syntax, particularly subordinate clauses. Some difficult examples of relative clauses are discussed which may anticipate later developments. Adverbial and complement clauses show that the optative, while morphologically stable, is no longer used in certain syntactic contexts (the oblique optative has more or less disappeared). An overall assessment attempts to distinguish the synchronic and the diachronic conclusions: the thesis deliberately discussed both together. It points out some concrete results establishing some spurious Menandrean texts while discussing the status of Menander's dialect. The main conclusion is that the terms of the debate about Menander's language have been misconceived: 'Attic vs. 'Koiné' is a false dichotomy in fourth-century Attica.